Cas3 is a limiting factor for CRISPR-Cas immunity in Escherichia coli cells lacking H-NS - Majsec, Kristina; Bolt, Edward L.; Ivančić-Baće, Ivana (BioMed Central, 2016)
Background: CRISPR-Cas systems provide adaptive immunity to mobile genetic elements in prokaryotes. In many bacteria, including E. coli, a specialized ribonucleoprotein complex called Cascade enacts immunity by “an interference reaction" between CRISPR encoded RNA (crRNA) and invader DNA sequences called “protospacers”. Cascade recognizes invader DNA via short “protospacer adjacent motif” (PAM) sequences and crRNA-DNA complementarity. This triggers degradation of invader DNA by Cas3 protein and in some circumstances stimulates capture of new invader DNA protospacers for incorporation into CRISPR as “spacers” by Cas1 and Cas2 proteins, thus enhancing immunity. Co-expression of Cascade, Cas3 and crRNA is effective at giving E. coli cells resistance to phage lysis, if a transcriptional repressor of Cascade and CRISPR, H-NS, is inactivated (Δhns). We present further genetic analyses of the regulation of CRISPR-Cas mediated phage resistance in Δhns E. coli cells. Results: We observed that E. coli Type I-E CRISPR-Cas mediated resistance to phage λ was strongly temperature dependent, when repeating previously published experimental procedures. Further genetic analyses highlighted the importance of culture conditions for controlling the extent of CRISPR immunity in E. coli. These data identified that expression levels of cas3 is an important limiting factor for successful resistance to phage. Significantly, we describe the new identification that cas3 is also under transcriptional control by H-NS but that this is exerted only in stationary phase cells. Conclusions: Regulation of cas3 is responsive to phase of growth, and to growth temperature in E. coli, impacting on the efficacy of CRISPR-Cas immunity in these experimental systems.